The art of Toshiko Takaezu in the language of silence - Held, Peter 1951-; Takaezu, Toshiko 1922-2011 (Univ. of North Carolina Press, 2010)
Presents a series of essays about the life and accomplishments of the Japanese American artist, describing her work as a potter, her incorporation of Eastern and Western techniques, and her transition into abstract sculpture and installation art